Pengaruh Konsep Diri, Persepsi Profesi Guru, dan Kesejahteraan Guru Terhadap Minat Menjadi Guru Pada Mahasiswa Program Studi Pendidikan Ekonomi Universitas Bhinneka PGRI Tulungagung Tahun Akademik 2024 /2025 - Ika Putri; Nailariza Umami (Advances In Education Journal, 2025)
This research aims to determine the partial and simultaneous influence of self-conceptual variables, teacher profession perception, and teacher welfare on the interest of becoming a teacher in students of the Economic Education Study Program of Bhinneka University PGRI Tulungagung Academic Year 2024/2025. The method used is a quantitative approach with multiple linear regression analysis using the help of SPSS version 25. The research sample consists of 166 students from semesters 2, 4, 6, and 8. The results of the analysis show that partially variables self-concept, teacher's professional perception, and teacher welfare have a positive and significant effect on the interest in becoming a teacher, shown by tcalculated > ttable and the Sig. < 0,05. Simultaneously, all three of them also have a significant effect with the value of Fcalculated > Ftable and Sig. < 0,05. The Adjusted R Square value of 0,580 indicates that 58% of the variation in interest in becoming a teacher is influenced by these three variables, while the remaining 42% is influenced by other factors outside this study.